2013
DOI: 10.1107/s0108270113010913
|View full text |Cite
|
Sign up to set email alerts
|

The coordination chemistry of two symmetric double-armed oxadiazole-bridged organic ligands with copper salts

Abstract: Two new symmetric double-armed oxadiazole-bridged ligands, 4-methyl-{5-[5-methyl-2-(pyridin-3-ylcarbonyloxy)phenyl]-1,3,4-oxadiazol-2-yl}phenyl pyridine-3-carboxylate (L1) and 4-methyl-{5-[5-methyl-2-(pyridin-4-ylcarbonyloxy)phenyl]-1,3,4-oxadiazol-2-yl}phenyl pyridine-4-carboxylate (L2), were prepared by the reaction of 2,5-bis(2-hydroxy-5-methylphenyl)-1,3,4-oxadiazole with nicotinoyl chloride and isonicotinoyl chloride, respectively. Ligand L1 can be used as an organic clip to bind Cu(II) cations and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have been carried out to study the effect of external strain on the properties of NaNbO3. It is found that the strain induced by the homovalent ion (Li x Na 1−x NbO 3 , K x Na 1−x NbO 3 ) and hetrovalent (Na 0.5 Bi 0.5 )TiO 3 (xNBT) [8,9,[20][21][22][23][24][25][26], BaTiO 3 [17,18,[27][28][29] CaTiO 3 [30,31], SrTiO 3 [7], BiFeO 3 [32,33], PbTiO 3 [34], etc., showed improvement in the ferroelectric and piezoelectric properties alongwith stabilization of various crystal structure.…”
mentioning
confidence: 99%
“…Several studies have been carried out to study the effect of external strain on the properties of NaNbO3. It is found that the strain induced by the homovalent ion (Li x Na 1−x NbO 3 , K x Na 1−x NbO 3 ) and hetrovalent (Na 0.5 Bi 0.5 )TiO 3 (xNBT) [8,9,[20][21][22][23][24][25][26], BaTiO 3 [17,18,[27][28][29] CaTiO 3 [30,31], SrTiO 3 [7], BiFeO 3 [32,33], PbTiO 3 [34], etc., showed improvement in the ferroelectric and piezoelectric properties alongwith stabilization of various crystal structure.…”
mentioning
confidence: 99%